SENIOR HIGH SCHOOL STUDENTS’ PERCEPTIONS IN THE USE OF ELECTRONIC MEDIA IN NON-FORMAL EDUCATION CLASSROOM - Raharjo, Tri Joko; Sutarto, Joko; Shofwan, Imam; Harianingsih, (PEOPLE: International Journal of Social Sciences, 2020)
Communication and information technology are currently developing so fast. This development certainly has an impact on non-formal education students. Non-formal education students usually use conventional learning models. However, with the development of technology, non-formal education students are also familiar with social media, students tend to use smart applications on their cellphones and laptops to surf the internet. Learning methods for students in non-formal education are part of the teaching and learning process, a strategy so that students can understand the material delivered by the tutor. The use of learning methods supported by appropriate and appropriate media will facilitate students to achieve their competence. As the objective of this research is to quantitatively analyze the advantages and disadvantages of using e-learning which was chosen as an effective learning method for non-formal education students. The study was conducted with a survey of observation, identification, filling students' perceptions of the teaching method of tutors, learning variables, evaluation of learning outcomes, electronic media used. Students have the perception that learning to use e-learning is more beneficial because of freedom of choice of place, freedom of time, ease of access but the drawbacks are objective assessment and high quota costs.